2005
DOI: 10.1016/j.jaerosci.2004.11.014
|View full text |Cite
|
Sign up to set email alerts
|

New personal sampler for viable airborne viruses: feasibility study

Abstract: While various sampling methods exist for collecting and enumerating airborne bacteria and fungi, no credible methodology has yet been developed for airborne viruses. A new sampling method for monitoring the personal exposure to bioaerosol particles has recently been developed and evaluated with bacteria and fungi. In this method, bacterial/fungal aerosol is aspirated and transported through a porous medium, which is submerged into a liquid layer. As the air is split into numerous bubbles, the particles are sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 13 publications
(12 reference statements)
0
39
1
1
Order By: Relevance
“…The inter-sampler variation did not exceed 20% for all the tests. In our earlier study (Agranovski et al 2004c), we obtained about the same average recovery rate of Vaccinia virus when performing a short-term (5-min) sampling with the bubbler. The present finding allows extending the sampling period much further.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…The inter-sampler variation did not exceed 20% for all the tests. In our earlier study (Agranovski et al 2004c), we obtained about the same average recovery rate of Vaccinia virus when performing a short-term (5-min) sampling with the bubbler. The present finding allows extending the sampling period much further.…”
Section: Resultsmentioning
confidence: 77%
“…When challenged with the robust Vaccinia virus, the bubbler provided an 89% recovery after a 5-minute sampling (Agranovski et al 2004c). Although stress-sensitive Influenza virus recovered only at a 19% level (as reported in Agranovski et al 2004c), the "bubbling" technique showed promise, at least, for relatively stress-resistant viruses if they are collected during short-term intervals. This is remarkable given that viruses often exhibit much stronger response to stress than bacteria and fungi, making their collection from air environment especially challenging.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Although known to be inefficient in collecting submicrometer-sized aerosols (Hogan et al, 2005), the BioSampler has been used as a reference sampler for many virus aerosol studies (e.g., Lednicky and Loeb [2013] and Dybwad et al [2014]). Additionally, impinger-based collection methods often inactivate viruses, especially "stress-sensitive viruses," reducing the usefulness of data acquired by these methods (Agranovski et al 2005). Hence, comprehensive understanding of the risk of airborne IFV transmission is limited by a lack of efficient samplers for the collection of airborne particles containing infectious influenza virus.…”
Section: Introductionmentioning
confidence: 99%
“…A new personal sampler has been developed and verified to be a very efficient tool for monitoring of viable airborne bacteria, fungi, and viruses (Agranovski et al 2002a(Agranovski et al , 2002b(Agranovski et al , 2005. The operation principle is based on aspiration of an air sample through peripheral holes located on the upper part of the sampler with following passing of air through porous media submerged into the layer of collecting liquid.…”
Section: Introductionmentioning
confidence: 99%